Home  
NSFW Content 
User Rankings  
Original Content  Channels 
Funny Pictures  Funny Videos 
Funny GIFs  YouTube Videos 
Text/Links  RSS Feeds 
4chan (4)
By: User has deleted their account.
90% of math
graduates can' t
solve this equation
graduates can' t
solve this equation
...
 
What do you think? Give us your opinion. Anonymous comments allowed.
#1

godtherapist ONLINE (12/31/2013) [+] (14 replies)
See what happens here is 10% of "Math Graduates" are ******* retarded and they have a solution for an impossible equation.
#40

crazyolitis (01/01/2014) [+] (3 replies)
I've got vacation right now. I refuse to do this **** .
#3

edwardtrollington (12/31/2013) [+] (7 replies)
Correct me if I'm wrong, but isn't the answer (positive or negative) infinity? (positive or negative) Infinity plus two is still (positive or negative) infinity.
#42

ubisoft (01/01/2014) []
It cancels itself out. You need to get y by itself but when you subtract the Ys they cancel and that's it no solution.
#118

snickets (01/01/2014) [+] (3 replies)
y+2=y
Since y contains the variable to solve for, move it to the left hand side of the equation by subtracting y from both sides
y+2y=0
Since y and y are like terms, add y to get y to get 0
0+2=0
Remove the 0 from the polynomial, adding or subtracting 0 doesn't change the value of the expression
2=0
Since 2=/=0, there are no solutions
Since y contains the variable to solve for, move it to the left hand side of the equation by subtracting y from both sides
y+2y=0
Since y and y are like terms, add y to get y to get 0
0+2=0
Remove the 0 from the polynomial, adding or subtracting 0 doesn't change the value of the expression
2=0
Since 2=/=0, there are no solutions
#56

kambin (01/01/2014) [+] (22 replies)
Let a=b Multiply both sides by a giving:
a*a=a*b Now add a*a to both sides giving:
a*a + a*a = a*a + a*b Or, rewritten:
2a*a = a*a + a*b Now subtract 2a*b from both sides
2a*a  2a*b = a*a + a*b  2a*b Combine like terms on right
2a*a  2a*b = a*a  a*b Factor out the a*a  a*b on each side
2(a*a  a*b) = 1(a*a  a*b) Cancel the (a*a  a*b) from both sides
2=1
a*a=a*b Now add a*a to both sides giving:
a*a + a*a = a*a + a*b Or, rewritten:
2a*a = a*a + a*b Now subtract 2a*b from both sides
2a*a  2a*b = a*a + a*b  2a*b Combine like terms on right
2a*a  2a*b = a*a  a*b Factor out the a*a  a*b on each side
2(a*a  a*b) = 1(a*a  a*b) Cancel the (a*a  a*b) from both sides
2=1
#152

cadencee (01/01/2014) []
That's like saying: 'The cat is two inches taller than itself' then expecting a mathematical solution. It's a statement, nothing more.
#51

lasomacintosh (01/01/2014) [+] (21 replies)
Y is equal to infinity because infinity plus 2 is still infinity.
#163

theswede (01/01/2014) []
I'm on winter break, I don't need to see math even if it involves dicks
#139

ideae (01/01/2014) [+] (12 replies)
y + 2 = y
y  y = 2
(11) y = 2
y=2/(11) = 2/0 = lim x > 1 (x+1)/(x1) = lim x > 0 (x+2)/x = 1+ 2/0 = 1 + 2/(2*0) = 1 + 1/0
let u = 1/0, y = 2u = 1+u => u = 1 => y = 2.
Or,
zeta(1) = 1 + ½ + ⅓ + ¼ + 1/5 + 1/6 + 1/7 + ⅛ + 1/9 + … + 1/n + …
= ln 0
y/2 = ½ + ¼ + 1/6 + ⅛ + … + 1/2n + …
y  2*y/2 = 1½+⅓¼+…+1/n (1)^(n+1) + … = ln 2
y = (ln 2)/0
let s = 1/0 = 1/(11) = 1+1^1+1^2+1^3+1^4+…=1+1+1+1+1+…
let t = ½ = 1/(1(1))= 11+11+11+11+…
t = 1+11+11+11+1…
s  t = 1+1+1+1+1+1+1+1+…
1+11+11+11+11+…
= 2+2+2+2+2+2+2+2+… [summing up each individual term]
= 2s
=> 1/0 = s = t = ½
=> y = (ln 2)/2. q.e.d.
y  y = 2
(11) y = 2
y=2/(11) = 2/0 = lim x > 1 (x+1)/(x1) = lim x > 0 (x+2)/x = 1+ 2/0 = 1 + 2/(2*0) = 1 + 1/0
let u = 1/0, y = 2u = 1+u => u = 1 => y = 2.
Or,
zeta(1) = 1 + ½ + ⅓ + ¼ + 1/5 + 1/6 + 1/7 + ⅛ + 1/9 + … + 1/n + …
= ln 0
y/2 = ½ + ¼ + 1/6 + ⅛ + … + 1/2n + …
y  2*y/2 = 1½+⅓¼+…+1/n (1)^(n+1) + … = ln 2
y = (ln 2)/0
let s = 1/0 = 1/(11) = 1+1^1+1^2+1^3+1^4+…=1+1+1+1+1+…
let t = ½ = 1/(1(1))= 11+11+11+11+…
t = 1+11+11+11+1…
s  t = 1+1+1+1+1+1+1+1+…
1+11+11+11+11+…
= 2+2+2+2+2+2+2+2+… [summing up each individual term]
= 2s
=> 1/0 = s = t = ½
=> y = (ln 2)/2. q.e.d.
also buying wet dream potions